2017
DOI: 10.1038/s41598-017-11012-7
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin links CFTR to TLR4 signaling to orchestrate anti-bacterial immune response in macrophages

Abstract: Macrophages (MΦs) with mutations in cystic fibrosis transmembrane conductance regulator (CFTR) have blunted induction of PI3K/AKT signaling in response to TLR4 activation, leading to hyperinflammation, a hallmark of cystic fibrosis (CF) disease. Here, we show that Ezrin links CFTR and TLR4 signaling, and is necessary for PI3K/AKT signaling induction in response to MΦ activation. Because PI3K/AKT signaling is critical for immune regulation, Ezrin-deficient MΦs are hyperinflammatory and have impaired Pseudomonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 62 publications
1
35
1
Order By: Relevance
“…A third limitation is that this study does not demonstrate the mechanism by which ivacaftor decreases monocyte IFN-γ sensitivity. Ivacaftor may be acting by a CFTR-dependent mechanism, as has been described for other cystic fibrosis-related myeloid cell defects [11,12]. Ivacaftor could also act directly on monocytes by a CFTR-independent mechanism; recent studies observed that CFTR modulators may have immune-dampening effects on macrophages that lack modulator-susceptible CFTR mutations [12,13].…”
mentioning
confidence: 88%
“…A third limitation is that this study does not demonstrate the mechanism by which ivacaftor decreases monocyte IFN-γ sensitivity. Ivacaftor may be acting by a CFTR-dependent mechanism, as has been described for other cystic fibrosis-related myeloid cell defects [11,12]. Ivacaftor could also act directly on monocytes by a CFTR-independent mechanism; recent studies observed that CFTR modulators may have immune-dampening effects on macrophages that lack modulator-susceptible CFTR mutations [12,13].…”
mentioning
confidence: 88%
“…The members of the ezrin/radixin/moesin (ERM) family proteins are involved in multiple physiological and pathological phenomenon by acting as cross-linkers between actin cytoskeleton and plasma membrane in polarized cells [4][5][6][7] . As the founding member of the ERM, ezrin is essential for cell migration 8 , inflammatory response regulation 9 , villus morphogenesis 10 and gastric acid secretion [11][12][13][14] . It has also been proved to be an important marker for cancer metastasis 15,16 .…”
mentioning
confidence: 99%
“…TLR4 trafficking and its regulation at the plasma membrane of MFs is altered in CF (Zhang et al, 2013). CF MFs also show blunted induction of the PI3K/AKT signaling pathway in response to LPS or P. aeruginosa (Zhang et al, 2015;Di Pietro et al, 2017). Wegiel et al (2014a) have shown that modulation of the HO-1/CO pathway or exogenous delivery of CO increases the efficiency of MFs in killing bacteria such as Escherichia coli and Enterococcus faecalis.…”
Section: Co Stimulates Cellular Host Defense Against Infections: Implmentioning
confidence: 99%
“…Several dysfunctional mechanisms may account for the blunted HO-1 induction in CF cells ( Figure 3 ). Our group has demonstrated that HO-1 is inefficiently induced in human and murine CF MΦs in response to inflammatory or infectious triggers, which correlate with exaggerated inflammation and prolonged inflammatory signaling ( Zhang et al., 2013 ; Zhang et al., 2015 ; Di Pietro et al., 2017 ). We have also shown that the defective induction of HO-1 is due to blunted activation of the PI3K/AKT pathway downstream of toll-like receptor 4 (TLR4) activation in MΦs from CF mouse models and patients with CF.…”
Section: Ho-1 Dysregulation In Cfmentioning
confidence: 99%
See 1 more Smart Citation